2020
DOI: 10.3390/app10144743
|View full text |Cite
|
Sign up to set email alerts
|

Assessing SMEs’ Internationalisation Strategies in Action

Abstract: In this paper, a structured review was conducted to investigate the internationalisation process of small and medium enterprises (SMEs) to define barriers and enablers and identify research gaps in this relevant field. Data were collected from two databases of scientific peer-reviewed articles (i.e., Scopus and Web of Science). After the selection process, 161 papers focusing on SMEs’ internalisation were analysed using both descriptive and content analysis. The analysis of the results highlights that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 162 publications
1
21
0
Order By: Relevance
“…The previous literature emphasizes the main role of globalization in the success of small and small enterprises (Brodowska-Szewczuk, 2019;Castagna et al, 2020). Various factors preventing the internationalization of SMEs have been empirically studied to examine environmental, socioeconomic, operational, and organizational barriers.…”
Section: Sustainable Management For Green Competitiveness Is Based On Various Theoretical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous literature emphasizes the main role of globalization in the success of small and small enterprises (Brodowska-Szewczuk, 2019;Castagna et al, 2020). Various factors preventing the internationalization of SMEs have been empirically studied to examine environmental, socioeconomic, operational, and organizational barriers.…”
Section: Sustainable Management For Green Competitiveness Is Based On Various Theoretical Aspectsmentioning
confidence: 99%
“…Various factors preventing the internationalization of SMEs have been empirically studied to examine environmental, socioeconomic, operational, and organizational barriers. Previous research has found that small and medium-sized companies are more effective when they are using good internal capital or when they get benefits and/or funding from external sources (Castagna et al, 2020). Moreover, a new approach to research aims at exploring the main success factors which have a positive effect on the internationalization of SMEs brings up a discussion about the prospect of intensifying the mechanism of internationalization for SMEs based on daily business-to-business relations with corporations.…”
Section: Sustainable Management For Green Competitiveness Is Based On Various Theoretical Aspectsmentioning
confidence: 99%
“…It seems clear in the extant literature that the concepts of universal and contextbound factors are used very broadly and interchangeably to describe one situation or another, and the boundary of what is considered 'universal' is widened or narrowed according to a specific authors' focus [13]. For example, in Sadeghi et al's [13,16] study, the 'universal' focus is largely on comparing two countries: a developing country with an emerging market (Iran) and a developed one (Italy). Furthermore, the importance of institutional development over time in entrepreneurial internationalization in emerging markets is often overlooked with an overemphasis on cross-sectional analyses [16].…”
Section: Contextual and Universal Factors In Emerging And Developed C...mentioning
confidence: 99%
“…For example, in Sadeghi et al's [13,16] study, the 'universal' focus is largely on comparing two countries: a developing country with an emerging market (Iran) and a developed one (Italy). Furthermore, the importance of institutional development over time in entrepreneurial internationalization in emerging markets is often overlooked with an overemphasis on cross-sectional analyses [16]. A general model of SME internationalization would be needed to broadly embrace the gradual process of internationalization of developing countries globally [14].…”
Section: Contextual and Universal Factors In Emerging And Developed C...mentioning
confidence: 99%
“…SMEs in Indonesia play an important role in the national economic system, including (1) the expansion of employment opportunities and the demand for labor, (2) the formation of gross domestic product (GDP), and (3) the provision of safety nets, especially for enabling low-income people to carry out economically productive activities [15]. In addition, the efficiency and effectiveness of this process is directly related to the way SMEs apply new knowledge and information related to local, regional, national, and global markets [16][17][18] to advance their business activities [19,20].…”
Section: Introductionmentioning
confidence: 99%